POTENTIAL OF Avicennia alba AS AN AGENT OF PHYTOREMEDIATION HEAVY METAL (Pb and Cu) IN WONOREJO, SURABAYA - R Rachmawati; Defri Yona; Rarasrum Dyah Kasitowati (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2018)
One of the regions in Surabaya which has accumulated the largest pollution levels was the region of Wonorejo. Wonorejo is an area that is used as a mangrove conservation. But, Pb and Cu are heavy metals that have been detected in high concentration in this region. Avicennia alba has been known to have the ability to absorb heavy metals so that mangrove can be used us phytoremediation agent. The purposes of this research were to analyze the concentration of heavy metals (Pb and Cu) in sediments, roots and leaves of Avicennia alba; to understand the potential of Avicennia alba as an agent of phytoremediation. The result showed that Cu concentration was higher than Pb concentration in sediment, roots and leaves. The concentrations of Cu were 4.13 ppm - 36.95 ppm and Pb between 3.28 ppm - 23.79 ppm. Based on bioconcentration factor (BCF) Avicennia alba was categorize as excluder (BCF1) of both heavy metals, but concentration of translocation factor (TF) of Pb was categorized phytoexstraction (TF1) and Cu was categorized phytostabilization (TF1). The result of the BCF and TF showed that Avicennia alba can absorb heavy metals (Pb and Cu) from the environment, however the mobility of the heavy metals in the mangrove will experience different phytoremediation mechanisms (phytostabilization for Cu; phytoexstraction for Pb).POTENTIAL OF AVICENNIA ALBA AS AN AGENT OF PHYTOREMEDIATION HEAVY METAL (PB AND CU) IN WONOREJO, SURABAYAABSTRACTOne of the regions in Surabaya which has accumulated the largest pollution levels was the region of Wonorejo. Wonorejo is an area that is used as a mangrove conservation. But, Pb and Cu are heavy metals that have been detected in high concentration in this region. Avicennia alba has been known to have the ability to absorb heavy metals so that mangrove can be used us phytoremediation agent. The purposes of this research were to analyze the concentration of heavy metals (Pb and Cu) in sediments, roots and leaves of Avicennia alba; to understand the potential of Avicennia alba as an agent of phytoremediation. The result showed that Cu concentration was higher than Pb concentration in sediment, roots and leaves. The concentrations of Cu were 4.13 ppm - 36.95 ppm and Pb between 3.28 ppm - 23.79 ppm. Based on bioconcentration factor (BCF) Avicennia alba was categorize as excluder (BCF1) of both heavy metals, but concentration of translocation factor (TF) of Pb was categorized phytoexstraction (TF1) and Cu was categorized phytostabilization (TF1). The result of the BCF and TF showed that Avicennia alba can absorb Pb and Cu from the environment, however the mobility of the heavy metals in the mangrove will experience different phytoremediation mechanisms (phytostabilization for Cu; phytoexstraction for Pb).Keywords: Avicennia alba, Phytoremediation, Factor Bioconcentration, Factor Translocation, Heavy Metal (Pb and Cu)